Problem of completeness of maximal topological groups - Arnautov , V. I.; Zelenyuk , E. G. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
Under the assumption of Booth's lemma a negative solution is obtained for Arnautov' s problem: is it true that each nondiscrete topology on a group can be strengthened to a discrete complete one?